Analisis Semiotika C.S. Pierce dalam Siniar Horor Kanal Lentera Malam dan Obrolan Santai - Mitrayudasi, Sangkary Asihta; Geraldine, Allesandra (PT. Impola Toba Lendt, 2024)
This article discusses C.S. Pierce's semiotic analysis of icons and symbols in horror podcasts on the Lentera Malam and Obrolan Santai channels. The writing technique uses a qualitative descriptive technique, which describes the discussion based on the dialog or conversation in the podcast. The semiotic approach is used as an analytical approach to explore a sign as a representation of objects, events, circumstances, feelings, and conditions in a broad culture. The podcasts to be analyzed are entitled (1) Pengalaman Metafisik Dokter Forensik, (2) Cerita Horor Perawat Rumah Sakit Terseram. Each podcast will be analyzed using the theory of icons and symbols. There are 14 forms of icons and 16 forms of symbols in the Pengalaman Metafisik Dokter Forensik and Cerita Horor Perawat Rumah Sakit Terseram podcast. Icons are seen in the words berdeham, bayangan, jenazah, dna, penampakan, cicicit-cicicit. Symbols are seen in the words penunggu, merinding, mimpi, pasien, mr. x, indigo.